Sistema de monitoreo de temperatura, humedad y control de agua para cultivos del invernadero n°2 del Campus Salache. - Chango Ortiz, Rolando Rigoberto (2021)
This technological proposal was carried out in the sector of Salache, Cotopaxi Province, with the objective of designing and implementing an automated system for the control of humidity and temperature in a greenhouse, which allowed us to control the climatological variables that vary according to the type of crop. The system is made up of electrical and electronic equipment such as PLC S7 1200, energy analyzer Sentron PAC 2200, temperature, humidity and level sensors, which allowed us to perform the control manually and automatically. The system consists of three solenoid valves distributed by sections, two 1 Hp pumps that will work to obtain the optimum pressure, to reduce the use of water the process of drip irrigation and sprinkling will be carried out. For the remote operation, a graphic interface (HMI) was used for the greenhouse personnel, which, according to the behavior of the climatological variables that occur in the greenhouse, can carry out the control and monitoring actions. The implementation of the automated system for temperature and humidity control improved the efficiency of the irrigation system and also helped us to save water resources; therefore, it could be a very useful project not only for the students of the Salache campus, but also for the agricultural sector of the province, since it improves its productivity in this area.